Effects of High Hydrostatic Pressure assisted degreasing on the technological properties of insect powders obtained from Acheta domesticus & Tenebrio molitor. (March 2021) - Bolat, Berkay; Ugur, Ahmet Erdem; Oztop, Mecit Halil; Alpas, Hami
Abstract: In this study, two edible insect species; Acheta domesticus (house cricket) and Tenebrio molitor (yellow mealworm) were defatted using different extraction methods and characterized afterwards. The main goal of the study was to see the effect of High Hydrostatic Pressure ( HHP ) extraction at different temperatures on the functional properties of the insect powders. Protein content, solubility, water and oil binding capacity; total phenolic content and antioxidant activity were all effected from the extraction method. Results showed that, temperature increase from 30 to 40 °C caused a decrease in the protein solubility of both powders. NMR relaxometry was used to interpret the gelation behavior and FTIR spectroscopy showed absorbance peaks mainly in amide I, amide II and amide III regions for both species. Results confirmed that HHP can be used for defatting purposes and could improve the functional properties of the powders to be used as a food additive in formulations. Highlights: HHP treatment caused an increase in TPC of both mealworm and cricket powders. Covalent type interactions were higher in cricket powder compared to mealworm. Mealworm powder is capable of retaining higher moisture than cricket powder. T2 relaxation times were used to explain gelling behavior and 'salt effect' on the powders.